2010
DOI: 10.1177/0042085910377433
|View full text |Cite
|
Sign up to set email alerts
|

Families and Home Computer Use: Exploring Parent Perceptions of the Importance of Current Technology

Abstract: Many families today have access to computers that help them with their daily living activities, such as finding employment and helping children with schoolwork. With more families owning personal computers, questions arise as to the role they play in these households. An exploratory study was conducted looking at parents whose children were enrolled in a Southern California elementary school. The study’s purpose was to examine parent perceptions of the importance placed on computer usage for themselves and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…The majority of parents do not see this use as negative, they consider digital technologies as important tools for the professional future of their children and as source of learning (mainly informal at such a young age, as there is not much articulation with school activities) (Ortiz, Green, & Lim, 2011;Plowman, McPake, & Stephen, 2008).…”
Section: Factors and Perceptions That Influence The Usage Of Digital mentioning
confidence: 99%
“…The majority of parents do not see this use as negative, they consider digital technologies as important tools for the professional future of their children and as source of learning (mainly informal at such a young age, as there is not much articulation with school activities) (Ortiz, Green, & Lim, 2011;Plowman, McPake, & Stephen, 2008).…”
Section: Factors and Perceptions That Influence The Usage Of Digital mentioning
confidence: 99%
“…The presence of students is also an important factor in the adoption of Internet at home as found by Newburger (2001) using survey data from the US, and Van Rompaey, Roe, and Struys (2002) using survey data from Belgium. This could happen because students ask for ICT, or because parents believe that ICT has educational benefit to their offspring, as Robertson, Soopramanien, and Fields (2004) found in the UK and Ortiz and Green (2011) found in the U.S. For example, more than 90% of parents in Ortiz and Green (2011) thought that access to a computer at home will have a positive effect on their children's success in life. The number of children in a household (which can be reflected by household size) was also found to be positively associated with Internet adoption (Rappoport, Kridel, Taylor, Alleman, & Duffy-Deno 2003;Savage & Waldman 2005).…”
Section: Effect Of Having Students In a Householdmentioning
confidence: 99%
“…Despite the increasing adoption rates of mobile technology, parents also acknowledge some uncertainty regarding how best to navigate the incorporation of multiple mobile devices into their children's daily lives. For example, Ortiz, Green, and Lim (2011) found that parents viewed current technology as important to their child's academic and future job success, whereas findings from several studies suggest parents worry about the negative impact of media on their child (Lampard, Jurkowski, & Davison, 2013a; Padilla-Walker, 2006), particularly regarding physical activity and especially when considering the impact of video games (Wartella, Rideout, Lauricella, & Connell, 2014). As these technological devices become more prevalent in family life, it is likely that the parent's resolution of these competing beliefs may influence how they choose to regulate their child's access to media.…”
mentioning
confidence: 99%